Título de la tesis: El derecho a la defensa como garantía básica del debido proceso frente a las decisiones de la Junta Cantonal de Protección de Derechos del GAD municipal del cantón Riobamba. - Sancho Saa, Britanny Gabriela (2024)
ABSTRACT: The right to defense is a right recognized as fundamental that, together with the other basic guarantees of due process, protects and ensures that the parties within a judicial or administrative process obtain the opportunity to be heard and present their arguments; in this sense, the Board Cantonal Protection of Rights of the city of Riobamba, being an administrative body empowered to immediately protect the individual and collective rights of people included in the priority attention group, must be subject to due process before issuing an executive protection measure. The present research work is focused on determining whether the right to defense is fulfilled in the face of the decisions given through administrative measures of the Cantonal Board for the Protection of Rights of the Riobamba canton; for this, inductive and legal methods will be used dogmatic and legal-descriptive; finally, the technique applied will be the survey. As a result, it was determined that within the Cantonal Board for the Protection of Rights of Riobamba processes, the parties need to be guaranteed effective enjoyment of their rights, especially that relating to due process and within it as a guarantee of the right to defense. , this is because the existing rules regarding the procedures that must be followed in the different cases of threat and violation of rights are often omitted by the members; in the same way, these errors are attributed to the excessive procedural burden and the lack of training of the three members of the Board in the city of Riobamba.